Foucault, Velázquez and the place of sacramentality - Carlsson, Petra (Studia theologica, 2015)
This article discusses Michel Foucault's analysis of Diego Velázquez' Las Meninas and suggests that Foucault's analysis introduces an erratic, yet material space for human knowledge after the death of God and man alike. The article introduces the space for thought provided by the Foucault analysis and subsequently relates it to Christian sacramentality of the postmetaphysical tradition with Catholic theologian Louis-Marie Chauvet. Chauvet, the article shows, underlines the materiality and situatedness of knowledge and thought in Christian faith in ways that relate to but also differ from the space Foucault points out in his analysis. With Foucault, the article argues, we may approach a more far reaching materiality that, in turn, may affect our account of sacramentality. The final part of the article, thus initiates an exploration of a material sacramentality in relation to the concrete, yet erratic space for human knowledge introduced by Foucault.